Self-assemblies of γ-CDs with pentablock copolymers PMA-PPO-PEO-PPO-PMA and endcapping via atom transfer radical polymerization of 2-methacryloyloxyethyl phosphorylcholine - Lin, Jing; Kong, Tao; Ye, Lin; Zhang, Ai-ying; Feng, Zeng-guo (Beilstein Journal of Organic Chemistry, 2015)
Pentablock copolymers PMA-PPO-PEO-PPO-PMA synthesized via atom transfer radical polymerization (ATRP) were self-assembled with varying amounts of γ-CDs to prepare poly(pseudorotaxanes) (PPRs). When the concentration of γ-CDs was lower, the central PEO segment served as a shell of the micelles and was preferentially bent to pass through the γ-CD cavity to construct double-chain-stranded tight-fit PPRs characterized by a channel-like crystal structure. With an increase in the amount of γ-CDs added, they began to accommodate the poly(methyl acrylate) (PMA) segments dissociated from the core of the micelles. When more γ-CDs were threaded and slipped over the segments, the γ-CDs were randomly distributed along the pentablock copolymer chain to generate single-chain-stranded loose-fit PPRs and showed no characteristic channel-like crystal structure. All the self-assembly processes of the pentablock copolymers resulted in the formation of hydrogels. After endcapping via in situ ATRP of 2-methacryloyloxyethyl phosphorylcholine (MPC), these single-chain-stranded loose-fit PPRs were transformed into conformational identical polyrotaxanes (PRs). The structures of the PPRs and PRs were characterized by means of 1H NMR, GPC, 13C CP/MAS NMR, 2D 1H NOESY NMR, FTIR, WXRD, TGA and DSC analyses.
Keywords: ATRP; γ-CD; double-chain-stranded; pentablock copolymer; poly(pseudorotaxane); polyrotaxane; single-chain-stranded

(untitled) - Harada, A.; Li, J.; Kamachi, M. (Nature, 1994)

(untitled) - Harada, A.; Kamachi, M. (Macromolecules, 1990)

(untitled) - Jiang, R.; Kong, T.; Ye, L.; Zhang, A.-y.; Feng, Z.-g. (Acta Polym. Sin., 2015)

(untitled) - Harada, A.; Li, J.; Kamachi, M. (Chem. Lett., 1993)

(untitled) - Okumura, H.; Kawaguchi, Y.; Harada, A. (Macromolecules, 2001)

(untitled) - Kawaguchi, Y.; Nishiyama, T.; Okada, M.; Kamachi, M.; Harada, A. (Macromolecules, 2000)

(untitled) - Kida, T.; Kikuzawa, A.; Akashi, M. (Chem. Lett., 2008)

(untitled) - Miura, T.; Kida, T.; Akashi, M. (Macromolecules, 2011)

(untitled) - Tamura, A.; Yui, N. (Chem. Commun., 2014)

(untitled) - Wang, J.; Li, S.; Ye, L.; Zhang, A.-y.; Feng, Z.-g. (Macromol. Rapid Commun., 2012)

(untitled) - Takahashi, A.; Katoono, R.; Yui, N. (Macromolecules, 2009)

(untitled) - Jiang, L.; Ye, L.; Zhang, A.-y.; Feng, Z.-g. (Macromol. Chem. Phys., 2014)

(untitled) - Kong, T.; Ye, L.; Zhang, A.-y.; Feng, Z.-g. (Beilstein J. Org. Chem., 2014)

(untitled) - Kong, T.; Lin, J.; Ye, L.; Zhang, A.-y.; Feng, Z.-g. (Polym. Chem., 2015)

(untitled) - Gao, P.; Wang, J.; Ye, L.; Zhang, A.-y.; Feng, Z.-g. (Macromol. Chem. Phys., 2011)

(untitled) - Gao, P.; Wang, J.; Wang, P.-J.; Ye, L.; Zhang, A.-y.; Feng, Z.-g. (Macromol. Chem. Phys., 2012)

(untitled) - Shuai, X.-T.; Porbeni, F. E.; Wei, M.; Bullions, T.; Tonelli, A. E. (Macromolecules, 2002)

(untitled) - Matyjaszewski, K.; Xia, J. (Chem. Rev., 2001)

(untitled) - Zhang, X.; Zhu, X.; Tong, X.; Ye, L.; Zhang, A.-Y.; Feng, Z.-G. (J. Polym. Sci., Part A: Polym. Chem., 2008)

(untitled) - Li, J.; Li, X.; Toh, K. C.; Ni, X.; Zhou, Z.; Leong, K. W. (Macromolecules, 2001)

(untitled) - Xiong, D.; Deng, Y.; Wang, N.; Yang, Y. (Appl. Surf. Sci., 2014)

(untitled) - Su, Y.-l.; Wang, J.; Liu, H.-z. (Macromolecules, 2002)

(untitled) - Wang, J.; Wang, P.-J.; Gao, P.; Jiang, L.; Li, S.; Feng, Z.-G. (Front. Mater. Sci., 2011)

(untitled) - Li, J.; Ni, X.; Zhou, Z.; Leong, K. W. (J. Am. Chem. Soc., 2003)